Microwave assisted radiant hybrid sintering of YMnO3 ceramic: Reduction of microcracking and leakage current. Issue 7 (May 2018) - Kumar, Manish; Phase, D.M.; Choudhary, R.J.; Upadhyay, S.K.; Reddy, V.R.
Abstract: In this study, YMnO3 (YMO) ceramics were successfully synthesized through microwave assisted radiant heating (MARH) method. Different microwave powers (0%, 15%, 30% and 50%) were employed during MARH synthesis of YMO ceramics. Detailed structural, magnetic and electrical leakage current properties of the synthesized samples were investigated. MARH has led to reduction of microcracking in YMO ceramic samples. A significant decrease in leakage current density is also observed for the YMO samples when microwave power is applied during MARH. This study clearly suggests that MARH is a facile and effective method to synthesize multiferroic ceramics like YMO for technological applications.